Adolescent Girls in Distress : a Guide for Mental Health Treatment and Prevention. - Choate, Laura Hensley (Springer Publishing Company, 2014)
""Contemporary culture promotes a 'hot and sexy' diva image to girls, encouraging inner emptiness, depression, and even risk for self-injury, but Adolescent Girls in Distress is exactly 'what the doctor ordered'- a well-researched, thoughtful, and systematic antidote empowering professionals to create the resilience, resourcefulness, and resistance needed to navigate and thrive in this girl-toxic culture. A must-read for anyone concerned about today's girls.""--Margo Maine, PhD, FAED, CEDS, . Eating Disorder Specialist and Author. Cultural stressors are affecting girls at increasingly younger.